Self‐Assembled Nanohelixes Driven by Host‐Guest Interactions and Metal Coordination - Lou, Xin‐Yue; Zhang, Kun; Bai, Yujie; Zhang, Siyuan; Li, Yuanyuan; Yang, Ying‐Wei (Angewandte Chemie, 2025)
Helical nanostructures fabricated via the self‐assembly of artificial motifs have been a captivating subject because of their structural aesthetics and multiple functionalities. Herein, we report the facile construction of a self‐assembled nanohelix (NH) by leveraging an achiral aggregation‐induced emission (AIE) luminogen (G) and pillar[5]arene (H), driven by host–guest interactions and metal coordination. Inspired by the “sergeants and soldiers” effect and “majority rule” principle, the host–guest complexation between G and H is employed to fixate the twisted conformation of G for the generation of “contortion sites”, which further induced the emergence of helicity as the 1D assemblies are formed via Ag(I) coordination and hexagonally packed into nano‐sized fibers. The strategy has proved feasible in both homogeneous and heterogeneous syntheses. Along with the formation of NH, boosted luminescence and enhanced productivity of reactive oxygen species (ROS) are afforded because of the efficient restriction on G, indicating the concurrent regulation of NH′s morphology and photophysical properties by supramolecular assembly. In addition, NH also exhibits the capacity for bacteria imaging and photodynamic antibacterial activities against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The self‐assembly of an achiral AIEgen driven by host–guest interactions and Ag(I) coordination gave rise to well‐defined nanohelixes, where the “contortion sites” produced by pillararenes enabled the helicity. Boosted luminescence and enhanced ROS productivity were achieved, allowing for applications in bacteria imaging and photodynamic antibacterial activities.